2014
DOI: 10.1007/s10784-014-9255-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of treaty legality and domestic institutional hurdles on environmental treaty ratification

Abstract: We study the effects of treaty design and domestic institutional hurdles on the ratification behavior of states with respect to multilateral environmental agreements (MEAs). Specifically, we examine whether (1) strong legality mandated by a treaty such as precisely stated obligations, strong monitoring/enforcement mechanisms, and dispute resolution procedures, and (2) high domestic constitutional hurdles such as requirements for explicit legislative approval deter countries from ratifying a treaty. To test our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 57 publications
0
47
0
Order By: Relevance
“…The following article focuses primarily on a combination of the first and the second cluster. That is, previous work has repeatedly shown that democracies are more likely than other regime types to cooperate via and commit to international environmental treaties (e.g., Mansfield, Milner and Rosendorff, 2002;Neumayer, 2002a;Pevehouse, 2006, 2008;Bättig and Bernauer, 2009;Lantis, 2009;Bernauer et al, 2010;Bernauer, Böhmelt and Koubi, 2013;Spilker and Koubi, 2016). Theoretically, Mattes and Rodríguez (2014, p.528) summarize that " [d]emocracies' superior track record [in international cooperation] is usually attributed to three institutional factors [...]: accountability of leaders, limited decision-making flexibility, and transparency."…”
Section: Introductionmentioning
confidence: 99%
“…The following article focuses primarily on a combination of the first and the second cluster. That is, previous work has repeatedly shown that democracies are more likely than other regime types to cooperate via and commit to international environmental treaties (e.g., Mansfield, Milner and Rosendorff, 2002;Neumayer, 2002a;Pevehouse, 2006, 2008;Bättig and Bernauer, 2009;Lantis, 2009;Bernauer et al, 2010;Bernauer, Böhmelt and Koubi, 2013;Spilker and Koubi, 2016). Theoretically, Mattes and Rodríguez (2014, p.528) summarize that " [d]emocracies' superior track record [in international cooperation] is usually attributed to three institutional factors [...]: accountability of leaders, limited decision-making flexibility, and transparency."…”
Section: Introductionmentioning
confidence: 99%
“…A third area focuses on describing and explaining institutional interplay and dynamics of regime complexes (Keohane & Victor 2011, Oberthür & Stokke 2011. Fourth, we see more sophisticated use of the methodological repertoire of social science, including qualitative comparative analysis (Stokke 2012), statistics (Spilker & Koubi 2016), game theory (Barrett 2003), and agent-based modeling (Hovi et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Making agreements legally binding seems not to help. Spilker & Koubi (2016), Böhmelt & Spilker (2016), and some other studies find that treaties characterized as hard law tend to deter or prevent ratification, particularly in systems requiring a supermajority. Focusing on outcomes rather than outputs, Breitmeier et al (2011) report negative correlations between legally binding rules and regime effectiveness.…”
Section: Regime Outcomes: Behavioral Changementioning
confidence: 94%
“…75 To the extent that MEAs permit the exercise of state discretion in determining the level of commitment or action on the basis of capacity (sometimes referred to as contextual differentiation) then those commitments may also be described as "soft" or, at the very least, demonstrating modern "variations" of "hard law". 76 Arguably this blurring of hard and soft law has been taken to a whole new level in the 2015 Paris Agreement, which uniquely (thus far) permits states to unilaterally determine their level of commitment in respect of reducing greenhouse gas emissions and/or enhancing sinks in light of the overall target of restricting temperature rise to no more than two degrees Celsius. 77 Whilst the Paris Agreement itself is clearly legally binding (in contrast to, for example, the 2009 Copenhagen Accord) there is uncertainty as to whether the nationally determined contributions (NDCs) are themselves legally binding with some commentators arguing that they are legally binding 78 and others suggesting that the NDCs themselves are not but the various administrative obligations associated with them…”
Section: Blurring the Distinction Between Soft And Hard Lawmentioning
confidence: 99%